Trade, not aid? The emerging donor strategy and its implications for Africa’s agrifood systems - Omamo, Steven Were; Kedir, Abbi (International Food Policy Research Institute, 2025)
Key messages 1. The United States is shifting its development engagement in Africa from aid to trade, emphasizing commercial partnerships, private sector development, and export-oriented growth. This shift is not unique to the United States; similar trends are being seen in Europe, China, and Japan, reflecting a global swing toward trade-first or business development strategies. 2. If well aligned, this approach can reinforce African priorities as defined in the Comprehensive Africa Agriculture Development Programme (CAADP) 2026–2035 Strategy, the Kampala Declaration, and national agricultural investment plans. Trade-first strategies map directly onto CAADP’s six strategic objectives, including agro-industrialization, food security, inclusivity, resilience, financing, and governance. 3. These strategies can also support implementation of the African Continental Free Trade Area, especially through investment in trade corridors, logistics, standards systems, and regulatory cooperation. However, there are risks of misalignment if initiatives prioritize donor or investor interests over inclusive transformation, public goods provision, and food systems resilience. 4. As articulated in discussions during the recent 4th International Conference on Financing for Development, consensus is building for Africa to move beyond aid and propel growth through private sector development. 5. African governments and partners must also go beyond coordination and seriously consider the institutional and political work required to steer this opportunity toward the public good. This consideration will require investing in regulatory capacity, protecting public goods, confronting corruption and capital flight, and ensuring that trade and investment flows are transparent, accountable, and inclusive. Without this, trade-first strategies risk reinforcing existing inequalities, undermining food systems resilience, and turn-ing agrifood transformation into an elite project. 6. Strategic statecraft—rooted in evidence, integrity, and public accountability—is essential to ensure that this shift delivers not just markets but also meaningful structural transformation through industrial policy. 7. The pivot to “trade, not aid” by global partners reflects a broader retreat from long-term development commitments. But it must also be recognized as a shift in priority from shared development outcomes to strategic self-interest, market capture, and influence. 8. Africa cannot be viewed as an open market to be carved up, claimed, or divided. African countries must insist on strategic alignment, mutual accountability, and respect for national development priorities—or risk having their food systems and economic futures being shaped by agendas that do not serve them.